STRATEGI POLITIK; PREFERENSI PARTAI POLITIK MENGHADAPI PEMILU DI ARAS LOKAL - Tinov, MY. Tiyas; Handoko, Tito (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This paper aims to outline the political situation and the political strategy of political parties inthe face of political contestation in the realm of local politics. This article objectively theunderlying thoughts on some of the problems faced by political parties, namely; First, that themajority of political parties have not been able to build a party structure to the deepest levelslower in real terms, and the Second, political parties tend to show the face of the managementof the party that the conventional / traditional, less utilize information technology systems andthe lack of measuring instruments used by political parties in facing political contest, especiallyin the realm of local politics. Moreover, political parties also have not been able to demonstrateclearly the number of cadres, Party members and sympathizers at various levels of the partystructure. This paper on the theory of thought underlying political strategy Peter Schroder. Inthe data-collection efforts, this paper emphasizes the qualitative data acquisition with a literaturestudy. The study concludes that the political strategy that can be done by political parties in theface of political contest local include strategic political mapping, preparation of planning,building resources, analysis of internal and external environment, strategize major influencevoting behavior, mobilization, imaging and coordination.